2003
DOI: 10.1021/ma034139g
|View full text |Cite
|
Sign up to set email alerts
|

Gel-to-Solid Transition in Polyethylene from the Viewpoint of the Crystallization Process

Abstract: The crystalline phase in gels and solid gel-derived samples of ultrahigh molecular weight polyethylene was studied using the infrared spectroscopy, low-frequency Raman spectroscopy and wideangle X-ray scattering methods. The spectroscopic data evidence the presence in gels of tiny crystallites whose thickness (3-5 nm) depends on the sort of the solvent used and it is insensitive neither to the concentration of the diluted solution, nor to the molecular weight of the polymer. After removal of the solvent, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…As a result of using a procedure for breaking down asymmetry reflections into two separate Gaussian components [13,16], it was found that the overall profile of the reflection is in good agreement with the experimentally observed profile. The calculated parameters of both components for reflection [200] are shown in Table 1.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…As a result of using a procedure for breaking down asymmetry reflections into two separate Gaussian components [13,16], it was found that the overall profile of the reflection is in good agreement with the experimentally observed profile. The calculated parameters of both components for reflection [200] are shown in Table 1.…”
supporting
confidence: 68%
“…A more detailed analysis of previously obtained x-ray diffraction data showed [13,[15][16]] that equatorial reflections [110] and [200] exhibit asymmetry. The barely perceptible asymmetry in the x-ray pattern of the gel becomes important when the solvent is eliminated (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At low λ, the folds of lamellar crystallites probably do not straighten, and lengthening of the fibre is basically due to straightening of chain segments binding adjacent microcrystallites in the gel fibre [9]. The structural model of the physical UHMPE gel that we used in the interpretation was taken from [11]. The only melting peak in the thermogram (T 1 ) at small λ should be assigned to crystallites in folded chains (FCC).…”
mentioning
confidence: 99%
“…The crystalline nature of the chain fixers in PE gels was supported by the IR and Raman spectroscopic studies. 3 In this light, the properties of crystallites in gelled polymer could determine, to some extent, the capability of the given gel solution to yield high performance fibers after a routine drawing process. In this communication, the characteristics of crystalline substance in a series of xerogels obtained from the powders of ultra-high-molecular-weight PE (UHMW PE) with different technological prehistory were studied with the help of the low-frequency Raman spectroscopy, which provides the information on the length distribution of straight chain segments (SCS) in linear polymers.…”
Section: Introductionmentioning
confidence: 99%